1997
DOI: 10.1021/js970143s
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for Prevention of Methionine Oxidation in Recombinant Monoclonal Antibody HER2

Abstract: Recombinant humanized monoclonal antibody HER2, rhuMAb HER2, in liquid formulations undergoes oxidation when exposed to intense light and elevated temperatures (30 & 40 degrees C). Met-255 in the heavy chain of the Fc region of the antibody is the primary site of oxidation. Met-431 of the Fc fragment can also be oxidized under extreme conditions. The amount of oxidation was determined by cleaving the Fab and Fc fragments by papain digestion, and the oxidized Fc fragment was detected by hydrophobic interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
207
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(216 citation statements)
references
References 15 publications
8
207
1
Order By: Relevance
“…This result supports the hypothesis by Lam et al [7], which suggested that a singlet oxygen formed from the reaction between molecular oxygen and photo-activated polysorbate-20 reacts with Met to form an intermediate, which reacts with a second Met leading to the formation of two Met sulfoxides. Polysorbate is commonly used in formulations.…”
Section: Distribution Of the Oxidized Met Residues In The Samples Expsupporting
confidence: 92%
See 2 more Smart Citations
“…This result supports the hypothesis by Lam et al [7], which suggested that a singlet oxygen formed from the reaction between molecular oxygen and photo-activated polysorbate-20 reacts with Met to form an intermediate, which reacts with a second Met leading to the formation of two Met sulfoxides. Polysorbate is commonly used in formulations.…”
Section: Distribution Of the Oxidized Met Residues In The Samples Expsupporting
confidence: 92%
“…The susceptibility of these Met residues was demonstrated by incubating the antibodies in liquid formulation either with [3,5,6] or without [6,7] the addition of a mild oxidizing reagent, tBHP. Lam et al [7] reported that exposure to high intensity fluorescence light also increased the level of Met oxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously observed that protein oxidation can be effectively inhibited by antioxidants like Met. [60][61][62] Since the stability of some proteins has been shown to be affected when formulated with certain antioxidants, the antioxidant should be carefully selected for each protein. We conducted additional work to screen excipients that would improve the chemical stability of the otelixizumab product formulated with PS80.…”
Section: Discussionmentioning
confidence: 99%
“…Several different types of antioxidants (Met, Cys, Glut, MTG, and EDTA) were selected and tested based on the presence in marketed protein formulations and their mechanism of action. [60][61][62][63][64][65] Results from our stability studies demonstrate that incorporation of Met and EDTA as antioxidants in the PS80 formulation substantially improved the stability of this mAb and provided protection from oxidation without altering the protein structure and solution properties. These data also suggested that oxidation occurs not only through a peroxide-mediated pathway, but also through a metal-catalyzed reaction and highlighted the value of a combination approach toward ensuring a stable formulation.…”
Section: Discussionmentioning
confidence: 99%